Language Attitude and Language Choice towards English by the Second Year Students of English Education Study Program of Palangka Raya University - Linda Astuti (The Study Program of English Education of Palangka Raya University, 2021)
This research was conducted to investigate students’ language attitude and language choice to know the language use of the students in learning English. The method used in this research was descriptive qualitative. The sample was taken from the second year students of English Education Study Program of Palangka Raya University in academic year 2019/2020. The data were collected through online questionnaire and structured interview which was designed to find out the students responses related to their language attitude on English and the language choice on certain variables such as setting, gender, participant, and topic. The result showed that the students committed to the positive attitude on English which was shown through their statement in either questionnaire responses or interviews. The students argued that English is important to be mastered, and they also committed to the importance of using English in classroom activities and in verbal communication of the formal contexts. In academic environment contexts, the students mostly used English as the main language but outside of the context they were more comfortable to use Bahasa Indonesia and even local languages